Computation of erosion in a hydro turbine. Issue 4 (5th October 2021) - Ghenaiet, Adel
Abstract : Purpose: This study aims to investigate the trajectories of sand particles and erosion wear in a hydraulic turbine model. Design/methodology/approach: The Lagrangian-based approach is used to track large numbers of sand particles and determine their impact through the hydro turbine components. The tracking procedure includes the stochastic eddy interaction model and the squeeze film effect. The number of particles, sizes and release positions are conformed to the particle concentration and size distribution. The impact locations, frequency and conditions of impacts are used to estimate the erosion rates and thereby the eroded mass from the distributor vane and the rotor blade and their deteriorated geometry. Findings: The patterns of erosion in the stationary and rotating parts differ significantly and the effect of the initial position of the runner blade is elucidated. The distributor vane is characterized by a widespread of erosion over the pressure side. Typically, the surface beyond the throat and the root and tip junctions are the regions prone to erosion wear. The entry region of the runner blade is subject to a high number of impacts resulting in high erosion rates visible from the forepart of the blade pressure side. Practical implications: The erosion patterns and geometry deterioration may serve to evaluate the drop in the hydraulic performance and to select the appropriate surface coating to extend the lifetime of the turbomachinery parts and reduce the maintenance cost. Originality/value: Erosion developments reveal a strong dependence on the blade position against the distributor vane and the particle size and concentration level.